(untitled) (Research, Society and Development, 2024)
Wheat flour is essential in baking and confectionery, and its quality depends on factors such as moisture content, which affects the durability and sensory properties of products. Controlling this parameter is crucial to guarantee the useful life of the product and its compliance with current standards. In this context, the general objective of this article is to investigate the moisture content in the production of wheat flour at company alpha as a parameter of quality and compliance with current standards. This study investigated the moisture content in three types of wheat flour produced by Alpha company, as a quality parameter. The results showed that common flour had 13.60% ± 0.251 moisture, self-raising flour had 13.11% ± 0.398, and breadmaking flour had 13.47% ± 0.294. All types were below the maximum limit of 15%, according to the standards of the Ministry of Health and MAPA.